Effect of Genially-Based Computational Chemistry Media on Students’ Motivation and Learning Outcomes in Chemical Bonding - Dinda Suci Ramadhani; Devi Patricia Hutagalung; Asep Wahyu Nugraha (Universitas Pendidikan Mandalika, 2026)
This study was motivated by the low level of students’ motivation and learning outcomes in chemical bonding material at SMA Negeri 13 Medan, as indicated by low participation, limited conceptual understanding, and many students not achieving the minimum learning criteria. This study aimed to examine the effect of Genially-based computational chemistry media on students’ learning outcomes and to describe students’ learning motivation after its implementation. This research employed a quasi-experimental method with a pretest–posttest control group design. The sample consisted of 70 students, divided into an experimental class (n = 35) and a control class (n = 35). The experimental class was taught using Genially-based computational chemistry media integrated with discovery learning, while the control class used discovery learning without the media. The data were analyzed using N-gain and an independent sample t-test. The results showed that the experimental class achieved a higher increase in learning outcomes (N-gain = 0.72, high category) compared to the control class (N-gain = 0.63, medium category). The hypothesis test indicated a statistically significant difference between the two groups (t (68) = 3.74, p < 0.05). In addition, students’ learning motivation in the experimental class was categorized as high (81%). In conclusion, Genially-based computational chemistry media has a significant effect on improving students’ learning outcomes and positively contributes to students’ learning motivation. Therefore, this media can be used as an innovative alternative in chemistry learning, particularly for abstract topics such as chemical bonding.